Activation characteristics of concrete shields containing colemanite - Yarar, Y (ELSEVIER SCIENCE BV, 1996)
This paper presents the theoretical results of the activation characteristics of a concrete shield containing colemanite, which is a boron-bearing mineral. Calculations are performed with a computer code, ANITA. The total activity and dose values of the shields with or without colemanite are compared for different continuous irradiation periods and neutron fluxes. The effect of colemanite on the activity is discussed by investigating the predominant radioisotopes at the shutdown radioactive inventory and the reactions that produce them.
Keywords: Materials Science; Nuclear Science & Technology